2011
DOI: 10.1029/2010jg001581
|View full text |Cite
|
Sign up to set email alerts
|

Water balance model for mean annual hydrogen and oxygen isotope distributions in surface waters of the contiguous United States

Abstract: [1] The stable H and O isotope composition of river and stream water records information on runoff sources and land-atmosphere water fluxes within the catchment and is a potentially powerful tool for network-based monitoring of ecohydrological systems. Process-based hydrological models, however, have thus far shown limited power to replicate observed large-scale variation in U.S. surface water isotope ratios. Here we develop a geographic information system-based model to predict long-term annual average surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
90
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(100 citation statements)
references
References 44 publications
9
90
0
1
Order By: Relevance
“…Immerzeel et al, 2010;Huss, 2011). Especially in ungauged catchments, but also in addition to quantitative studies, this method may be applied to evaluate glacier or permafrost contributions, or to observe winter / summer runoff ratios, as proposed by Bowen et al (2011). Finally, the CC-RCWIP-modelled seasonal amplitude of δ 18 O P was not correlated to the seasonal amplitude of δ 18 O R , which confirmed the results from the direct comparison of GNIP and GNIR station data (Fig.…”
Section: Comparison Of Water Stable Isotopes In Precipitation and Riverssupporting
confidence: 76%
See 3 more Smart Citations
“…Immerzeel et al, 2010;Huss, 2011). Especially in ungauged catchments, but also in addition to quantitative studies, this method may be applied to evaluate glacier or permafrost contributions, or to observe winter / summer runoff ratios, as proposed by Bowen et al (2011). Finally, the CC-RCWIP-modelled seasonal amplitude of δ 18 O P was not correlated to the seasonal amplitude of δ 18 O R , which confirmed the results from the direct comparison of GNIP and GNIR station data (Fig.…”
Section: Comparison Of Water Stable Isotopes In Precipitation and Riverssupporting
confidence: 76%
“…In general, the CC-RCWIP model results showed that averaged δ 18 O values in river water samples were strongly correlated with amount-averaged precipitation in the upstream catchment of a river station. This finding underscored that the average isotopic composition of river water reflected amountaveraged rainwater on a global scale, as was also observed regionally for the United States by Fekete et al (2006) and Bowen et al (2011). These model comparisons provided a comparative tool whereby isotopic deviations of rivers from average precipitation revealed natural or anthropogenic Figure 9.…”
Section: Gnir Data To Calibrate Isotope Precipitation Model(s)mentioning
confidence: 86%
See 2 more Smart Citations
“…Because the stable isotope composition of precipitation varies geographically (Dansgaard 1964, Bowen andWilkinson 2002), variation in the stable isotope composition of river water indicates the volume-weighted integration of source water within the watershed (Bowen et al 2011). The spatial variation of river water stable isotopes has been characterized at the continental scale from the USGS National Stream Quality Accounting Network (NASQAN, Coplen 2001, Dutton et al 2005).…”
Section: Introductionmentioning
confidence: 99%